2002
DOI: 10.1097/00005373-200204000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Early Use of Recombinant Factor VIIa Improves Mean Arterial Pressure and May Potentially Decrease Mortality in Experimental Hemorrhagic Shock: A Pilot Study

Abstract: Intravenous administration of rFVIIa early after induction of hemorrhage shortens prothrombin time and improves mean arterial pressure. A trend toward improved survival was observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
1
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 10 publications
0
31
1
1
Order By: Relevance
“…Recent data have shown that injection of recombinant activated FVII into swine increases mean arterial pressure. 35 FVII itself can also elicit cellular responses, such as angiogenesis 9 -11 and inflammation. 12,13,36 The blood coagulation cascade is initiated when cryptic tissue factor is expressed and exposed to circulating blood and binds plasma activated FVII.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data have shown that injection of recombinant activated FVII into swine increases mean arterial pressure. 35 FVII itself can also elicit cellular responses, such as angiogenesis 9 -11 and inflammation. 12,13,36 The blood coagulation cascade is initiated when cryptic tissue factor is expressed and exposed to circulating blood and binds plasma activated FVII.…”
Section: Discussionmentioning
confidence: 99%
“…All such studies, but one, have made use of liver injuries and associated hemorrhage. Four studies have involved normothermic pigs, an absence of hemodilution prior to injury, and did not supplement rFVIIa therapy with liver packing when liver injury was involved (Tables 8a,c; Lynn et al, 2002;Jeroukhimov et al, 2002;Schreiber et al, 2003;Pusateri et al, 2003). In one of these studies, resuscitation was used beginning 15 min postinjury (Schreiber et al, 2003), and at a rate lower than that used in the current study (100 mil/min).…”
Section: Discussionmentioning
confidence: 97%
“…Numerous anecdotal reports (Dutton, et al, 2004;Martinowitz, Kenet, Segal, & Lubetsky, 2001;O'Neill, et al, 2002) and animal models (Jeroukhimov, et al, 2002;Lynn, et al, 2002;Martinowitz, Holcomb, & Pusateri, 2001;Schreiber, et al, 2002) have generally supported the potential benefit of FVIIa to treat uncontrolled bleeding, and recent randomized trials indicated a trend toward higher survival among civilian trauma patients receiving FVIIa compared with standard care controls (Boffard, et al, 2005).…”
Section: Discussionmentioning
confidence: 99%